Emergency Basic Income during the Pandemic - Wispelaere, Jurgen De (Cambridge quarterly of healthcare ethics, 2021)
This paper focuses on an emergency basic income (EBI) as a tool for avoiding financial insecurity during the time of pandemic. The authors argue that paying each resident a monthly cash amount for the duration of the crisis would serve to protect them from the economic fallout.They suggest three reasons why the EBI proposal is particularly well-suited to play an important role in a comprehensive public health response to COVID-19: it offers an immediate and agile response; it prioritizes the most vulnerable in the affected population; and it promotes a solidaristic response to the pandemic crisis. To go beyond the need to shut down and restart an EBI assistance scheme each time a pandemic hits, the authors propose considering turning the program into a permanent feature.